Design of forward osmosis system - Wibisono, Y. (Elsevier Inc., 2019)
Forward osmosis (FO) is an emerging membrane process that has potential to be a "low-energy" footprint for water and wastewater treatment. However, the term "low energy" may only be suitable when FO is applied as a stand-alone process without requiring the draw solute recovery. This chapter discusses the design systems for FO implementation, either as a stand-alone system via the osmotic concentration or as a hybrid system for recovery of the draw solute. For applications requiring the draw solute recovery, the recovery unit contributes to the capital costs and the energy demand. This chapter discusses the design of FO system as a stand-alone process and design of process involving stand-alone FO system. The hybrid systems involving draw solute recovery are also discussed in great details, including the thermal process via evaporation, membrane distillation or crystallization, stimuli-response processes using "smart" draw solute, pressure-driven membrane process, and other recovery processes. Finally, the summary of the current reported system design and future research trend on FO system is also provided. Â© 2020 Elsevier Inc. All rights reserved.